Metathesis with alkanes elucidating reaction pathways - Núñez Zarur, Francisco (2021)
Spa: The building blocks of any siliceous material is SiO4 (quartz, microporous zeolites, amorphous silica)The Si-O-Si angle can be changed in the range 130°-180° without appreciable energetic cost. SiO4 units at the external surface of the silica material carry OH groups.